2006
DOI: 10.1002/cncr.22294
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of depression in cancer patients

Abstract: BACKGROUND. Inflammation and perturbation of the hypothalamic‐pituitary‐adrenal (HPA) axis function appears to play a putative role in the etiology of depression. Patients with metastatic cancer demonstrate elevated prevalence rates for depression. The objective of the current study was to illustrate the efficacy of interleukin‐6 (IL‐6) and HPA axis function as adjuncts to support the diagnosis of depression in cancer patients. METHODS. Plasma concentrations of IL‐6 and cortisol were measured in 114 cancer pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 50 publications
5
70
2
Order By: Relevance
“…This "bodymind" discrepancy is probably due to the denial of the negative affect, as too difficult to adapt to (or accept). The physiological indications are consistent with therapists' observation of excessive, difficult to control responses of cancer sufferers to fearful events, as well as with data showing that 30-40% of patients suffering from cancer simultaneously suffer depression and anxiety disorders (Bucceri, 1998;Jehn et al, 2006;Stommel, Given, & Given, 2002). The concept of "cancer proneness," "cancerous personality" or "personality susceptible to immunosuppression" assumes the tendency to repress emotional reactions to difficult life events (Dattore et al, 1980;Eysenc, 1985;Watson, Pettingale, & Greer, 1984).…”
Section: Introductionsupporting
confidence: 81%
“…This "bodymind" discrepancy is probably due to the denial of the negative affect, as too difficult to adapt to (or accept). The physiological indications are consistent with therapists' observation of excessive, difficult to control responses of cancer sufferers to fearful events, as well as with data showing that 30-40% of patients suffering from cancer simultaneously suffer depression and anxiety disorders (Bucceri, 1998;Jehn et al, 2006;Stommel, Given, & Given, 2002). The concept of "cancer proneness," "cancerous personality" or "personality susceptible to immunosuppression" assumes the tendency to repress emotional reactions to difficult life events (Dattore et al, 1980;Eysenc, 1985;Watson, Pettingale, & Greer, 1984).…”
Section: Introductionsupporting
confidence: 81%
“…[49][50][51][52] Relevant to the role of the immune system in depression in cancer patients, increased plasma concentrations of IL-6, have been found in two separate studies in cancer patients diagnosed with major depression (Table 1). 53,54 Nevertheless, results have been inconsistent, especially in studies looking at correlations between inflammatory biomarkers and depressive symptoms (as measured by standardized depression rating scales). Of note, however, there is a surprising paucity of studies on depressed cancer patients compared to the rich literature examining patients with other medical illnesses, including cardiovascular disease, as well as healthy depressed subjects, where a large number of studies have revealed a clear relationship between inflammatory markers and both a diagnosis of major depression and depressive symptom severity.…”
Section: Depressionmentioning
confidence: 99%
“…(Conti et al 2004;Terreni & De Simoni, 1998) and IL-6 has been linked to depressive spectrum behaviors characterized as "sickness behaviors" (Dantzer et al, 2002;Dantzer, 2006). Both IL-6 and hypercortisolemia have been linked to depression (Dowlati et al, 2010;Howren et al 2009;Liu et al 2011;Lopez-Duran et al 2009;Stetler & Miller, 2011) and disruption of cortisol rhythms has been linked to depression in breast and ovarian cancer populations (Abercrombie et al 2004;Jehn et al 2006);Lutgendorf et al 2008;Weinrib et al 2010) It is possible that the residual tumor mass may have affected both inflammatory pathways and self-reported functional outcomes. However, extent of surgical resection was not significantly associated with reduction of inflammation.…”
Section: Discussionmentioning
confidence: 99%